Size and aging effects on antimicrobial efficiency of silver nanoparticles coated on polyamide fabrics activated by atmospheric DBD plasma - Zille, Andrea (2015)
This work studies the surface characteristics, antimicrobial activity, and aging effect of plasma-pretreated polyamide 6,6 (PA66) fabrics coated with silver nanoparticles (AgNPs), aiming to identify the optimum size of nanosilver exhibiting antibacterial properties suitable for the manufacture of hospital textiles. The release of bactericidal Ag+ ions from a 10, 20, 40, 60, and 100 nm AgNPs-coated PA66 surface was a function of the particles’ size, number, and aging. Plasma pretreatment promoted both ionic and covalent interactions between AgNPs and the formed oxygen species on the fibers, favoring the deposition of smaller-diameter AgNPs that consequently showed better immediate and durable antimicrobial effects against Gram-negative Escherichia coli and Gram- positive Staphylococcus aureus bacteria. Surprisingly, after 30 days of aging, a comparable bacterial growth inhibition was achieved for all of the fibers treated with AgNPs <100 nm in size. The Ag+ in the coatings also favored the electrostatic stabilization of the plasma-induced functional groups on the PA66 surface, thereby retarding the aging process. At the same time, the size-related ratio (Ag+/Ag0) of the AgNPs between 40 and 60 nm allowed for the controlled release of Ag+ rather than bulk silver. Overall, the results suggest that instead of reducing the size of the AgNPs, which is associated with higher toxicity, similar long-term effects can be achieved with larger NPs (40−60 nm), even in lower concentrations. Because the antimicrobial efficiency of AgNPs larger than 30 nm is mainly ruled by the release of Ag+ over time and not by the size and number of the AgNPs, this parameter is crucial for the development of efficient antimicrobial coatings on plasma-treated surfaces and contributes to the safety and durability of clothing used in clinical settings.